Mechanochemical synthesis of Bi4Ti3O12 - Lazarević, Z. Ž [UNESP]; Stojanović, B. D. [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2006)
Our efforts were directed to the preparation of bismuth titanate - Bi 4e;Ti3O12 (BIT) by mechanically assisted synthesis. The mechanical activation was applied to prepare bismuth titanate, Bi4e;Ti3O12, from bismuth oxide, Bi 2O3, and titanium oxide, TiO2 (in an anatase crystal form). Mechanochemical synthesis was performed in a planetary ball mill in air atmosphere. Bismuth titanate ceramics was obtained by sintering at 1000° C The formation of Bi4e;Ti3O12 in the sintered samples was confirmed by X-ray diffraction analysis. Scanning electron microscopy, SEM, was used to study the particle size and powder morphology. The obtained results indicate that Bi4e;Ti3O12 from the powder synthesized by high-energy ball milling exhibits good sinterability, showing advantage of the mechanochemical process over conventional solid-state reaction.
Keywords: Ceramics; Mechanochemical synthesis; Milling; Powders; X-ray methods; Powder morphology; Ceramic materials; Scanning electron microscopy; Sintering; Synthesis (chemical); X ray analysis; Bismuth compounds